Case report: Is bilateral renal dioctophymosis and severe uremia in a dog synonymous of euthanasia? Not today - Caye, Pâmela; Gasparotto, Jean Carlos; Hörbe, Anna Vitória; Andrade, Letícia Rodrigues Leitao; Reinstein, Rainer da Silva; Mangini, Luiza Tonietto; Müller, Daniel Curvello de Mendonça; Brun, Maurício Veloso (Frontiers in Veterinary Science, 2024)
A dog with bilateral renal dioctophymosis presented with stage 5 acute kidney injury, weight loss, vomiting, apathy, and hematuria. Laboratory tests showed creatinine of 17.2 mg/dL and Dioctophyme renale eggs in the urine. It underwent a 30-minute session of hyperbaric oxygen preconditioning at a pressure of 2 ATA. Subsequently, bilateral nephroscopy was performed, without warm ischemia, using Amplatz-type renal dilators. Five parasites were removed, three females from the right kidney, one female from the left kidney, and one male from the abdominal cavity. After surgery, the patient continued doing daily hyperbaric oxygen therapy (HBOT) sessions and clinical therapy. Postoperative care consisted of analgesics, antimicrobials, antioxidants, gastric protector and fluid therapy. Ultrasound monitoring showed a reduction in the area of renal dilation and the hematological and biochemical tests showed rapid recovery from acute kidney injury. There was no bacterial growth in the urine sample collected directly from the kidneys. The patient had an excellent clinical progression and was discharged from hospital seven days postoperatively, with creatinine values of 2.9 mg/dL. This is the first report of the use of nephroscopy in the treatment of dioctophymosis and indicates excellent chances of cure even in severe cases of bilateral parasitosis. HBOT was shown to be an ally in the clinical therapy of patients with D. renale by helping with stabilization and postoperative recovery.